Alternative to traditional stretching methods for flexibility enhancement in well-trained combat athletes: local vibration versus whole-body vibration - Kurt, C. (Biology of Sport, 2015)
This study aimed to compare the effect of local vibration (LV) and whole body vibration (WBV) on lower body flexibility and to assess whether vibration treatments were more effective than traditionally used static and dynamic stretching methods. Twenty-four well-trained male combat athletes (age: 22.7 ± 3.3 years) performed four exercise protocols - LV (30 Hz, 4 mm), WBV (30 Hz, 4 mm), static stretching (SS), and dynamic stretching (DS) - in four sessions of equal duration 48 hours apart in a randomized, balanced order. During a 15-minute recovery after each protocol, subjects performed the stand and reach test (S&R) at the 15th second and the 2nd, 4th, 6th, 8th, 10th and 15th minute. There was a similar change pattern in S&R scores across the 15-minute recovery after each protocol (p = 0.572), remaining significantly elevated throughout the recovery. A significant main protocol effect was found for absolute change in S&R scores relative to baseline (p = 0.015). These changes were statistically greater in LV than WBV and DS. Changes in SS were not significantly different from LV, but were consistently lower than LV with almost moderate effect sizes. After LV, a greater percentage of subjects increased flexibility above the minimum detectable change compared to other protocols. Subjects with high flexibility (n = 12) benefited more from LV compared with other methods (effect size = 0.862). In conclusion, LV was an effective alternative exercise modality to acutely increase lower extremity flexibility for well-trained athletes compared with WBV and traditional stretching exercises.